2022
DOI: 10.1038/s41431-021-01016-3
|View full text |Cite
|
Sign up to set email alerts
|

Informing relatives of their genetic risk: an examination of the Belgian legal context

Abstract: Please check your article carefully, coordinate with any co-authors and enter all inal edits clearly in the eproof, remembering to save frequently. Once corrections are submitted, we cannot routinely make further changes to the article.2. Note that the eproof should be amended in only one browser window at any one time; otherwise changes will be overwritten.3. Author surnames have been highlighted. Please check these carefully and adjust if the irst name or surname is marked up incorrectly. Note that changes h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Other countries like Australia, Britain and France have legislation that allows healthcare professionals to disclose genetic information considered beneficial to family members in case the individual tested is not willing to do so [52][53][54]. While current Belgian legislation coupled, with international precedent, may provide sufficient justification to establish a duty to inform relatives of their genetic risk in some cases [55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other countries like Australia, Britain and France have legislation that allows healthcare professionals to disclose genetic information considered beneficial to family members in case the individual tested is not willing to do so [52][53][54]. While current Belgian legislation coupled, with international precedent, may provide sufficient justification to establish a duty to inform relatives of their genetic risk in some cases [55].…”
Section: Discussionmentioning
confidence: 99%
“…A significant amount of research has been conducted in the fields of genetics and genomics. Associated findings have contributed to the global debate on return of GGR results [9][10][11][12][13][14]. Although international policies for return of individual genetic research findings are still evolving, there is general consensus for feedback of results.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been recommended that it is imperative that the privacy and confidentiality of the person enrolling in the study should be respected but in cases where there is benefit in sharing results with family members, the original participant should grant permission because just like feedback to individuals, feedback should not be imposed on family members, but should be based on their voluntary consent [14]. A study involving REC chairpersons in the USA showed that 62% of the REC chairs agreed that participants should be informed that their results could be offered to family members and asked to indicate their choice, but such a statement may not be adequate informed consent [41].…”
Section: Discussionmentioning
confidence: 99%
“…A significant amount of research has been conducted with resultant literature and global debate on return of genetic and genomics testing results [9][10][11][12][13][14]. Despite the fact that international policies for return of individual genetic research findings are still evolving, general consensus appears to be that in order to consider findings for feedback a number of criteria need to be met including the ability to assess the evidence base for potentially disease causing genetic variants in relation to the concerned population(s); assessment of whether the particular finding is beneficial to the individual; ensuring that patients are appropriately informed of the implications of the findings for their disease or treatment, and referral for follow-up care while seeking guidance of the Research Ethics Committee (REC) [15].…”
Section: Introductionmentioning
confidence: 99%
“…In 2022, the European Journal of Human Genetics published an article by Amicia Philips, Thomas Bronselaer, Pascal Borry, Ine Van Hoyweghen, Danya F Vears, Laurent Pasquier and Stefaan Callens: ‘Informing relatives of their genetic risk: an examination of the Belgian legal context’ [ 1 ]. With an original and thought provoking insight into one of the most topical and relevant medico-legal challenges arising with the advent of a new genetic era, this article offers a well-informed and accessible analysis of the many ethical and legal issues presented in this area, as well as the practical questions arising for physicians in medical practice.…”
Section: Introductionmentioning
confidence: 99%